Removal of 20 Years Old Broken Tension Band Wires from United Patella Fracture: A Rare Surgical Case with Review of Literature - KC, Kapil Mani; Acharya, Parimal; Sigdel, Arun (Nepal Orthopaedic Association Journal, 2016)
Breakage of tension band wires used to treat patella fracture, several years after surgery, is not uncommon. Broken wires may migrate to surrounding neurovascular structures, other vital organs like heart and may cause potentially fatal complications. Once the wires have been broken, it may be difficult to remove the broken pieces of metal wires. We report a 50 years old male patient with broken tension band wires at multiple sites. The broken wires were removed 20 years after the initial surgery without any undue complications. However, the patient sustained significant soft tissue injury in the attempt to remove all the pieces of broken wires that could otherwise have been safely removed within a year after fracture union.